The Cambridge introduction to Walter Benjamin - Ferris, David S. 1954- (Cambridge University Press, 2008)
For students of modern criticism and theory, Walter Benjamin's writings have become essential reading. His analyses of photography, film, language, history, allegory, material culture, the poet Charles Baudelaire, and his vast examination of the social, political and historical significance of the Arcades of nineteenth-century Paris have left an enduring and important critical legacy. This volume examines in detail a substantial selection of his important critical writings on these topics from 1916 to 1940 and outlines his life in pre-war Germany, his association with the Frankfurt School, and the dissemination of his ideas and methodologies into a variety of academic disciplines since his death. David Ferris traces the development of Benjamin's key critical concepts and provides students with an accessible overview of the life, work and thought of one of the twentieth-century's most important literary and cultural critics
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Benjamin, Walter / 1892-1940 / Criticism and interpretation; Benjamin, Walter -- 1892-1940; Einführung